A longitudinal study of the lifestyle characteristics of adolescent with chronic fatigue symptoms - Yamada, Takayoshi; Demura, Shinichi; Shimada, Shigeru (International Journal of Health, 2013)
Fatigue is a complicated, multifactorial disorder that is poorly understood. Till date, many studies conducted have cross-sectionally analyzed the problem, but this fails to recognize the temporal nature of chronic fatigue that lasts over six months. This study aimed to examine the lifestyle characteristics of adolescents with chronic fatigue symptoms. In total, 462 healthy male students aged 15–19 years were enrolled to participate in a physical fitness test and surveys on subjective fatigue symptoms and lifestyle. They were assessed twice with a 1-year interval. Significant associations existed between both years in all parameters: for the low fatigue group (V = 0.45–0.66), except for regularity of bedtime and seasoning and for the high fatigue group (V = 0.45–0.73), except for regularity of the time of awakening, bedtime, and nutritional balance. Marked differences existed between the groups in the regularity of the time of awakening, nutritional balance, and seasoning (difference of V ? 0.2). All parameters tended to show inadequate lifestyle after a year in the high subjective fatigue symptom group. When compared with adolescents with low levels of fatigue, the lifestyles of adolescents with chronic fatigue changed more markedly and toward a more unhealthy or inadequate lifestyle.